Pengaruh Harga, Kualitas Produk, Dan Brand Image Terhadap Loyalitas Pelanggan Pesen Kopi Kota Malang (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Angkatan 2018 Universitas Islam Malang) - Fian Arifiona Faradila; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of price, product quality, and brand image on customer loyalty for coffee orders in the city of Malang, especially for FEB UNISMA students batch 2018. The data used in this study used primary data by distributing questionnaires to respondents. The research population is students of the Faculty of Economics and Business, UNISMA, while the sample used is the 2018 Islamic Management, Accounting and Banking Study Program at the Faculty of Economics and Business, Islamic University of Malang. The research sample was taken from the population using a sampling technique in the form of a random sampling method. The results obtained by using multiple linear regression and the test of this study used the f test and t test. The results of this study indicate that price, product quality and brand image partially affect customer loyalty. Meanwhile, simultaneously price, product quality and brand image affect customer loyalty. Keywords: Price, Product Quality, Brand Image, and Customer Loyalty